Honey on brain health: benefit or forfeit? - Arshad NA,; Nellysha Namela Mak,; Teoh, SL; Mohamad Fairuz Yahaya, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Brain health deterioration is a worldwide health epidemic. Alzheimer’s disease and other dementias are among the most expensive diseases to treat, with direct care expenses exceeding those for cancer and heart disease. The consumption of overly processed food products over the time has contributed to the increasing number of health deterioration at an earlier age. Honey has been known worldwide through history to be one of the purest, and popular natural product to be consumed as a health booster notably due to its antioxidant and phenolic contents. In the recent decade, many studies were perfomed to understand the biological process of cellular insult to the brain and ways to halt or slow down the process using natural products. Honey was shown in some of these studies as having the potential that may reduce or slow down these neural degenerations. Based on recent studies conducted on the use of honey and its effects on the brain physiologically, and anatomically, the results showed that honey holds potential in halting or even treating brain health deteriorations.